Association between Serum Uric Acid to HDL-Cholesterol Ratio and Nonalcoholic Fatty Liver Disease in Lean Chinese Adults. (23rd March 2020) - Zhang, Ya-Nan; Wang, Qin-Qiu; Chen, Yi-Shu; Shen, Chao; Xu, Cheng-Fu
Abstract : Background/Aim . The risk factors for nonalcoholic fatty liver disease (NAFLD) in lean population have not been fully clarified. This study aimed to explore the association between uric acid to HDL-cholesterol ratio (UHR) and NAFLD in lean Chinese adults. Methods . A cross-sectional study was performed among 6285 lean Chinese adults (body mass index < 24 kg/m 2 ) who took their annual health checkups. NAFLD was diagnosed based on hepatic ultrasound examination, with exclusion of other etiologies. Results . Of 6285 lean participants enrolled, 654 NAFLD cases were diagnosed. The overall NAFLD prevalence was 10.41%, and the prevalence was 15.45% and 7.16% in men and women, respectively. UHR was significantly higher in NAFLD patients than in controls (14.25 ± 5.33% versus 10.09 ± 4.23%, P < 0.001 ). UHR quintiles were positively associated with NAFLD prevalence, which was 1.91% in the first UHR quintile and increased to 3.58%, 7.81%, 14.17%, and 24.54% in the second, third, fourth, and fifth quintile groups, respectively (P < 0.001 for trend). Multivariate logistic regression analysis showed that UHR was independently associated with an increased risk of NAFLD (odds ratio: 1.105; 95% CI: 1.076–1.134; P < 0.001 ). Sensitivity analysis showed that UHR remained significantly associated with NAFLD in lean participants with normal range of serum uric acid and HDL-cholesterol levels. Conclusions . UHR was significantly associated with NAFLD and may serve as a novel and reliable marker for NAFLD in lean adults.